2007
DOI: 10.4102/hsag.v12i1.242
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting on contraceptive use among youth in northern Tshwane: Part 2

Abstract: Young people are vulnerable to risky behaviors that cause major health problems such as sexual behaviour resulting in early, unplanned pregnancy and sexually transmitted diseases (STDs) including human immunodeficiency virus (HIV). ABSTRAK Die jeug is besonder kwesbaar as gevolg van riskante gedrag wat groot gesondheidsprobleme soos seksuele gedrag veroorsaak wat tot seksueel oordraagbare siektes en VIGS mag lei. Hierdie studie is gedoen om die faktore wat ’n impak het op die gebruik van voorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Lack of sexual knowledge makes adolescents vulnerable when transferring from a restricted high school environment to a liberal environment, such as a university (Braun & Clarke, 2006) (Sweya et al, 2016). Maja (2007), advocates that contraceptives should be accessible everywhere to minimise barriers to their use, family planning and sexual knowledge. Maja (2007) claims that health-care professionals are not supportive to clients who needed reproductive health services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of sexual knowledge makes adolescents vulnerable when transferring from a restricted high school environment to a liberal environment, such as a university (Braun & Clarke, 2006) (Sweya et al, 2016). Maja (2007), advocates that contraceptives should be accessible everywhere to minimise barriers to their use, family planning and sexual knowledge. Maja (2007) claims that health-care professionals are not supportive to clients who needed reproductive health services.…”
Section: Discussionmentioning
confidence: 99%
“…Maja (2007), advocates that contraceptives should be accessible everywhere to minimise barriers to their use, family planning and sexual knowledge. Maja (2007) claims that health-care professionals are not supportive to clients who needed reproductive health services. The current study found that the unfriendly and judgmental attitudes of the campus health-care professionals contributed to students' pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…When school curriculums do not include subjects on sexuality and contraception, adolescents have to rely on their peers and the media for information on sexual health as indicated in the national information, education and communication situation survey [28,31]. Information from peers may not always be accurate as illustrated by this quote made by a male adolescent in a study carried out in South Africa "guys pretend to be knowing how to use condoms even when they don't" [36]. Education policies should therefore be reviewed to integrate more comprehensive and age specific messages on sexuality and reproductive health.…”
Section: Discussionmentioning
confidence: 99%